A composite policy tool to measure territorial resilience capacity. (June 2020) - Pontarollo, Nicola; Serpieri, Carolina
Abstract: The 2007–2008 global recession and consequent slow recovery have revealed considerable heterogeneity in economic performance across countries and regions. This study contributes innovatively to existing resilience literature by identifying a life cycle resilience framework and computing a "handy" composite Regional Economic Resilience Indicator. We analyse economic resilience by means of a cluster and exploratory spatial data analysis, revealing well-defined spatial patterns in the EU. National resilience trends dominate in the EU-15, while a more heterogeneous spatial pattern is present in the EU-13. Our findings can support the monitoring of economic resilience at regional level and facilitate a common understanding of this complex and dynamic process for policy purposes. Highlights: We characterize regional economic resilience as a complex process. The main dimensions of this process are synthetized into the Regional Economic Resilience Indicator. Spatial and cluster analyses identify economic resilience patterns across EU regions. Our composite tool is a potential instrument to draw policy implications.